Preparation and electromagnetic properties of nanosized ZnFe2O4 with various shapes. Issue 15 (15th October 2019) - Huang, Xiaogu; Qin, Yushuang; Ma, Yabin; Chen, Yunyun
Abstract: In this paper, nanosized ZnFe2 O4 with different morphologies were prepared by electrospinning method. The choice of initial parameters, such as PVP concentration, metal salt concentration, electrostatic voltage, calcination temperature and calcination rate, were investigated to prepare desired morphologies. The as-prepared samples exhibited various shapes of nano-particle, nano-rods, nano-beads and nano-fiber. The relationship between microstructure and electromagnetic properties was discussed in detail. It has been found that the saturation magnetization of ZnFe2 O4 ferrite not changed significantly with the various morphologies and the values were nearly 13 emu/g. However, the coercivity was varied with the different morphologies, and the maximum value of 48.79 Oe was observed in the ZnFe2 O4 nano-fiber. Moreover, the magnetic loss capacity of ZnFe2 O4 was improved with the enhancement of the morphology anisotropy. The various shaped ZnFe2 O4 can be promising lightweight microwave absorbers and it is significant to develop novel microwave absorption mechanism of ZnFe2 O4 ferrite.